Growth and characterization of thiosemicarbazide barium chloride [Ba(NH2NHCSNH2)Cl2]crystals: Novel potential NLO material. (2022) - Sankar, K.; Rajasekaran, R.; Sujatha, A.; Vetrivelan, V.
Highlights: Lower UV cutoff wavelength of 260 nm with throughout higher transmission in entire spectra. Higher SHG of TNSCBC has been found 1.21 times that of same particle size of KDP. Higher thermal stability and low dielectric loss. Crystal structure was analyzed by single crystal XRD and their functional groups are assigned by FTIR. TG/DTA studies were carried out to find the thermal stability of the material. Abstract: Semiorganic Nonlinear optical Crystals of Thiosemicarbazide Barium Chloride was grown by slow evaporation solution growth technique. The unit cell parameters were estimated by subjecting the crystal to single crystal X- ray diffraction. The Grown crystals were subjected to powder X- ray diffraction for analyzing the crystalline nature of the sample. The transmission spectrum of grown crystal was recorded by UV–Vis–NIR Spectrometer in the range between 200 nm and 800 nm which addressed the high percentage of transmission of the sample in the entire visible region. The presence of functional groups was studied by FT- IR analysis. Thermal Stability and melting temperature of the grown crystal was identified from TG –DTA analysis Dielectric behaviour of the grown crystal was studied and the results are discussed in detail. Second harmonic generation (SHG) conversion efficiency has been estimated as 1.21 times greater than potassium dihydrogen phosphate crystal.